The effect of cisplatin on the role of proprotein convertases (PCs) in human ovarian cancer cells - Boulay, Hillary Michelle (University of Ottawa (Canada), 2006)
Proprotein convertases (PCs) have been implicated in cancer progression as well as cell survival, although their role in ovarian cancer and drug sensitivity is largely unknown. Of all the PCs, PC4 has the most restricted expression; present only in reproductive tissues (testis, ovary and placenta). The expression and regulation of PC4 were investigated using a pair of cisplatin-sensitive and -resistant cell lines as an in vitro model of ovarian cancer. PC4 is expressed in the ovarian cancer cell lines as well as in tumours from patients diagnosed with the disease. Over-expression of PC4 in chemosensitive cells attenuated cisplatin (CDDP)-induced apoptosis, while inhibition of PC4 activity or down-regulation of PC4 by siRNA sensitized chemoresistant cells to the apoptotic effects of CDDP. Furthermore, current data suggests that the role of PC4 in chemoresistance may be mediated through the processing and activation of IGF-II. These data demonstrate for the first time that PC4 is anti-apoptotic and imply its involvement in the chemoresistance of human ovarian cancer cells.
Keywords: Biology, Cell.